Direct fluorescence in situ hybridization on human metaphase chromosomes using quantum dot-platinum labeled DNA probes - Hwang, Gyoyeon; Lee, Hansol; Lee, Jiyeon (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2015)
The telomere shortening in chromosomes implies the senescence, apoptosis, or oncogenic transformation of cells. Since detecting telomeres in aging and diseases like cancer, is important, the direct detection of telomeres has been a very useful biomarker. We propose a telomere detection method using a newly synthesized quantum dot (QD) based probe with oligonucleotide conjugation and direct fluorescence in situ hybridization (FISH). QD-oligonucleotides were prepared with metal coordination bonding based on platinum-guanine binding reported in our previous work. The QD-oligonucleotide conjugation method has an advantage where any sequence containing guanine at the end can be easily bound to the starting QD-Pt conjugate. A synthesized telomeric oligonucleotide was bound to the QD-Pt conjugate successfully and this probe hybridized specifically on the telomere of fabricated MV-4-11 and MOLT-4 chromosomes. Additionally, the QD-telomeric oligonucleotide probe successfully detected the telomeres on the CGH metaphase slide. Due to the excellent photostability and high quantum yield of QDs, the QD-oligonucleotide probe has high fluorescence intensity when compared to the organic dye-oligonucleotide probe. Our QD-oligonucleotide probe, conjugation method of this QD probe, and hybridization protocol with the chromosomes can be a useful tool for chromosome painting and FISH. (C) 2015 Elsevier Inc. All rights reserved.
Keywords: PEPTIDE NUCLEIC-ACID; TELOMERE LENGTH; FISH